2021
DOI: 10.1073/pnas.2025265118
|View full text |Cite
|
Sign up to set email alerts
|

Click chemistry–enabled CRISPR screening reveals GSK3 as a regulator of PLD signaling

Abstract: Enzymes that produce second messengers are highly regulated. Revealing the mechanisms underlying such regulation is critical to understanding both how cells achieve specific signaling outcomes and return to homeostasis following a particular stimulus. Pooled genome-wide CRISPR screens are powerful unbiased approaches to elucidate regulatory networks, their principal limitation being the choice of phenotype selection. Here, we merge advances in bioorthogonal fluorescent labeling and CRISPR screening technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…O-ClickFC can directly measure the abundance of de novo -synthesized PC by FACS at organelle resolution, which allows high-throughput CRISPR screening focused on subcellular PC distribution. Compared with recent examples of FACS-based CRISPR screens using lipid metabolism reporters such as fluorescent lipid (cholesterol)-binding proteins (Lu et al, 2022), phospholipase D activity-based click labeling (Bumpus et al, 2021), or a fluorescent PC analog (Maruoka et al, 2021), O-ClickFC offers a unique and unprecedented platform to elucidate uncertain links between PC metabolism and the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…O-ClickFC can directly measure the abundance of de novo -synthesized PC by FACS at organelle resolution, which allows high-throughput CRISPR screening focused on subcellular PC distribution. Compared with recent examples of FACS-based CRISPR screens using lipid metabolism reporters such as fluorescent lipid (cholesterol)-binding proteins (Lu et al, 2022), phospholipase D activity-based click labeling (Bumpus et al, 2021), or a fluorescent PC analog (Maruoka et al, 2021), O-ClickFC offers a unique and unprecedented platform to elucidate uncertain links between PC metabolism and the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, we have recently used IMPACT-enabled FACS enrichment as a phenotypic selection step in a genome-wide CRISPR interference screen to elucidate new regulators of PLD signaling (Figure 4A) (44). At a mechanistic level, these studies revealed glycogen synthase kinase 3 (GSK3) as a positive regulator of PKC-mediated PLD signaling via effects on de novo gene expression.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In practice, we chose to use CRISPR interference (CRISPRi) to perform knockdown due to the accessibility of genome-wide libraries and suitability for such screening, even for essential genes. Following FACS enrichment of desired cell populations, short guide RNAs (sgRNAs) enriched in each population were identified by next-generation sequencing, and this information led to the identification of genes whose knockdown modulated PLD activity (Figure C) …”
Section: Applications Of Impact For Biological Discoverymentioning
confidence: 99%